Situation analysis of riverside primary health care in the city of Manaus/AM – an experience report (Research, Society and Development, 2023)
The promotion of equity is one of the principles of the Unified Health System (SUS) and is directly related to the concepts of equality and social justice. In this context, the Riverside Family Health Teams (ESFR) and Riverside Family Health Teams (ESFF) emerge as adaptations of the public health system to the needs and specificities of an important part of the Brazilian population – the riverside people. The study is an experience report that approaches in a descriptive-reflexive way the impressions collected during a period of ten days in May 2022 by two medical students about the work carried out in a Basic Fluvial Health Unit (UBSF), responsible for serving the riverside communities of the lower Rio Negro, linked to the rural area of the Municipality of Manaus, in the state of Amazonas. Throughout the experience, it was possible to analyze the routine of a service highly adapted to the environmental and social environment in which it operates and the performance of a multidisciplinary team closely connected to local residents. Challenges and difficulties faced by UBSF Ney Lacerda were identified, some inherent to the practice of care in the population of the waters and others not generalizable, thus allowing a reflection on the need to create new strategies and restructuring of health programs aimed at specific populations.